2022
DOI: 10.1007/s00401-022-02482-9
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of cervid prions to humanized mice demonstrates the zoonotic potential of CWD

Abstract: Prions cause infectious and fatal neurodegenerative diseases in mammals. Chronic wasting disease (CWD), a prion disease of cervids, spreads efficiently among wild and farmed animals. Potential transmission to humans of CWD is a growing concern due to its increasing prevalence. Here, we provide evidence for a zoonotic potential of CWD prions, and its probable signature using mice expressing human prion protein (PrP) as an infection model. Inoculation of these mice with deer CWD isolates resulted in atypical cli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…It is unclear how representative the PMCA replication process is compared to natural conditions. A second very recent study has reported clinical disease in several CWD-inoculated tg650 mice [ 19 ]. Of concern, these clinical mice did not have consistent positive confirmatory tests for prion disease including immunohistochemistry, immunoblot, and RT-QuIC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is unclear how representative the PMCA replication process is compared to natural conditions. A second very recent study has reported clinical disease in several CWD-inoculated tg650 mice [ 19 ]. Of concern, these clinical mice did not have consistent positive confirmatory tests for prion disease including immunohistochemistry, immunoblot, and RT-QuIC.…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic mice genetically engineered to express human prion protein have proved to be an excellent tool for studying prion disease transmission. To date, eight groups including ours have tested the susceptibility of human prion protein-expressing mice to CWD infection [ 12 19 ]. Seven groups have reported no strong evidence for CWD transmission to humanized mice [ 12 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CWD transmission studies in transgenic mouse models expressing PrPs from various species including ovine, bovine, and human showed low or absent ability of CWD prions to cross relevant species barriers (Tamgüney et al 2009b ; Wilson et al 2012 ; Kurt et al 2015 ; Wadsworth et al 2022 ). Interestingly, a more recent study found atypical disease and fecal prion shedding in transgenic mice expressing human PrP when infected with deer prions, indicating zoonotic potential of CWD (Hannaoui et al 2022 ). In addition, transmission of CWD into non-human primates via the oral route (Marsh et al 2005 ; Race et al 2009 , 2018 ) and efficient in vitro conversion of human PrP by CWD prions (Barria et al 2011 ; Wang et al 2021 ) should also not be ignored.…”
Section: Prion Diseases Of Different Speciesmentioning
confidence: 99%
“…Thus, answering the question of whether or not CWD prions can infect humans is highly relevant. Conventional rodent infection studies from independent labs have reported failed attempts to transmit CWD prions to transgenic mice that overexpress human PrP (Kong et al 2005 ; Tamgüney et al 2006 ; Sandberg et al 2010 ; Wilson et al 2012 ; Kurt et al 2015 ; Race et al 2019 ; Wadsworth et al 2021 ) with the exception of a recent study (Hannaoui et al 2022 ). Using non-human primates, the Bartz group reported two squirrel monkeys that were intracerebrally challenged with CWD prions developed prion diseases and reached terminal stages in 31 and 34 months after infection (Marsh et al 2005 ).…”
Section: Applications Of Pmca To Understand Prion Biologymentioning
confidence: 99%